Bilateral Economic Impacts of China–Pakistan Economic Corridor - Tariq Ali; Jikun Huang; Wei Xie (Agriculture, 2022)
China is making large investments in Pakistan’s transport infrastructure under the China–Pakistan Economic Corridor. This study aims to quantitatively analyze the bilateral impacts of these investments through several policy scenarios in 2025 using a global economic model. Our results show that due to transport infrastructure development, the GDP and welfare of both Pakistan and China will improve, with a maximum of 0.3% and 0.01% increase in GDP, and USD 2.6 billion USD 1.8 billion gains in welfare for Pakistan and China, respectively. Regarding mutual trade, Pakistan’s total and agricultural exports to China will increase in the range of USD 9.6–13.7 billion and USD 4.7–6.6 billion, respectively. The percentage increase in Pakistan’s net exports of agricultural commodities to China will be higher than that of non-agricultural products. Pakistan will tap into China’s import demand for fresh fruits and vegetables and other perishable food products. Due to changing trade relations, Pakistan’s production structure will undergo slight structural adjustments. For Pakistan’s agriculture sector, the rice and fruit sectors will be top gainers, with 2.1–2.6% and 1.2–1.7% output expansion, respectively. Pakistan will also experience some leveling of income due to a relatively higher increase in wages of unskilled labor than skilled labor. The output of China’s rice sector will drop the most (−1–−1.3%). Overall, the effects on China’s economy are minimal. We suggest several critical policy recommendations in light of our results, especially for Pakistan.